Higher Cerebral Blood Flow Predicts Early Hematoma Expansion in Patients With Intracerebral Hemorrhage: A Clinical Study - Wang, Weijing; Jin, Weitao; Feng, Hao; Wu, Guoliang; Wang, Wenjuan; Jia, Jiaokun; Ji, Ruijun; Wang, Anxin; Zhao, Xingquan (Frontiers in Neurology, 2021)
Abstract: The early hematoma expansion of intracerebral hemorrhage (ICH) indicates poor prognosis. This paper studies the change of CBF around hematoma and its relationship with hematoma expansion in the acute stage of intracerebral hemorrhage. 50 patients with supratentorial cerebral hemorrhage were examined with CTP within 6 hours after the onset of the disease, and non-contrast CT was reexamined within 24 hours. Absolute ICH growth and relative ICH growth were calculated, respectively. An absolute increase in hematoma>12.5ml or relative growth>33% was considered to indicate significant hematoma expansion. The Ipsilateral peri-edema CBF and Ipsilateral edema CBF were calculated in patients with and without hematoma expansion by CTP maps, respectively. The incidence of hematoma enlargement in the early stage of supratentorial cerebral hemorrhage was 32%; The CBF of the hematoma expansion group was higher than that of the patients without hematoma expansion (23.54 ± 12.48 vs 15.14 ± 7.40, P = 0.004). After adjusting for age, gender, Symptom onset to NCCT and Baseline hematoma volume, ipsilateral peri edema CBF was still an independent risk factor for early HE (or = 1.095, 95% CI = 1.012-1.185, P = 0.024). Increased cerebral blood flow predicts early hematoma expansion in patients with intracerebral hemorrhage.